Pengaruh Kualitas Produk, Harga, dan Celebrity Endorser Terhadap Keputusan Pembelian Sepeda Motor Yamaha Matik New Mio M3 125 Di Kota Pontianak - B31112006, Harianto Japri (Jurnal Manajemen Update, 2016)
In the modern era such as this technology develops so rapidly and accompanied by an increase in the human population, causing the competition is so tight, it requires people to be able to apply the efficiency and effectiveness in all its activities, as well as in terms of mobility from one place to another. So that also affect the selection of means of transportation used, such as a motorcycle can be a mainstay in carrying out its activities and is considered the most effective and efficient. The purpose of this study was to determine the effect of product quality, price, and celebrity endorser on purchasing decisions. This research is associative where there is a relationship between several independent variables on the dependent variable. The population in this study are all consumers Yamaha in Pontianak. The sample in this study was 100 people who become purchasing decision makers as well as using new Yamaha motorcycle matic 125 mio m3 in Pontianak taken by purposive sampling. Data collection is done by using a questionnaire. Research shows that three independent variables are product quality, price, and celebrity endorser has a positive and significant impact on the dependent variable, namely purchasing decisions Yamaha motorcycle matic new 125 mio m3 in the city of Pontianak. The test results of multiple regression showed that all independent variables (product quality, price, and celebrity endorser) positive influence on purchase decisions. The positive influence most of the purchasing decisions Yamaha motorcycle matic new mio m3 125 in the city of Pontianak is variable celebrity endorser with a coefficient of 0.366, followed by the variable quality of the product with a coefficient of 0.349, while the variables that affect its lowest price variable with coefficient of 0.251. Keywords: purchasing decisions, product quality, price, celebrity endorser.